Catalytic oxidative dehydrogenation of malic acid to oxaloacetic acid. Issue 17 (1st August 2019) - Drif, Asmaa; Pineda, Antonio; Morvan, Didier; Belliere-Baca, Virginie; De Oliveira Vigier, Karine; Jérôme, François
Abstract : Here we report the oxidative dehydrogenation of malic acid to oxaloacetic acid, a key precursor in the fabrication of amino acids, over Pt–Bi/C catalysts. Abstract : Here we report the oxidative dehydrogenation of malic acid to oxaloacetic acid, a key precursor in the fabrication of amino acids, over Pt–Bi/C catalysts. Under optimized conditions, we discovered that OAA was selectively produced with up to 60% conversion ( i.e. 60% yield). The recurrent unwanted decarboxylation of OAA to pyruvic acid was circumvented by successfully conducting the catalytic reaction at 25 °C. A comparison with the classical Fenton oxidation reaction is discussed.